Efficient N2- and O2-Sensing Properties of PtSe2 With Proper Intrinsic Defects - Yong, Xin; Zhang, Jianqi; Ma, Xiangchao; He, Weiming (Frontiers in Chemistry, 2021)
Developing efficient N2 and O2 gas sensors is of great importance to our daily life and industrial technology. In this work first-principles calculations are performed to study the N2 and O2 gas sensing properties of pure and defected PtSe2. It is found that both N2 and O2 adsorb weakly on pure PtSe2, and adsorption of the molecules induces negligible changes in the electrical and optical properties. Whereas the Pt@Se anti-site defect significantly improves the N2 adsorption capacity of PtSe2 and induces notable change in the electrical property. Similar results are also observed for the Pt and Se vacancies, and Pt@Se anti-site defects when examining O2 adsorption. In addition, notable changes in the optical absorption spectra of PtSe2 with Pt@Se defect are induced upon N2 adsorption, which also occurs for PtSe2 with Pt and Se vacancies, and Pt@Se anti-site defects upon O2 adsorption. These results demonstrate that PtSe2 with the corresponding defects can be both excellent electrical and optical sensors for detecting N2 and O2 gases. Our work offers a new avenue for preparing efficient gas sensors.